MathGroup Archive 1996

[Date Index] [Thread Index] [Author Index]

Search the Archive

Integration Conundrum


Why does the following happen?

With parameters a and b in the expression:

In[38]:=
Integrate[E^s (-E^(a (-s+t)/2)+E^(b (-s+t)/2)),{s,0,1}]
Out[38]=
    (a t)/2      (b t)/2      (2 - a + a t)/2      (2 - b + b t)/2
-2 E          2 E          2 E                  2 E
----------- + ---------- + ------------------ - ------------------
  -2 + a        -2 + b           -2 + a               -2 + b


With actual values for a and b:


In[37]:=
Integrate[E^s (-E^((3 + 5^(1/2)) (-s+t)/2)+E^((3 - 5^(1/2)) 
(-s+t)/2)),{s,0,1}]
Out[37]=
           s   ((3 - Sqrt[5]) (-s + t))/2    ((3 + Sqrt[5]) (-s + t))/2
Integrate[E  (E                           - E                          ), 
 {s, 0, 1}]

This was tried on both Macintosh version 2.2.2 and HP/UX version 2.2.?.

Lee Larson   <>   http://www.louisville.edu/~lmlars01   <>   (502)339-8758
Mathematics Department, University of Louisville, Louisville, KY 40292 USA


==== [MESSAGE SEPARATOR] ====


  • Prev by Date: Re: Quality of Exported Graphics
  • Next by Date: Re: programming competition Correction
  • Previous by thread: Re: InterpolatingFunction
  • Next by thread: Re: programming competition Correction